Photo-curing insulation paste, preparation method thereof and application of photo-curing insulation paste in BC battery
By using polyurethane acrylate oligomers and fluorine-containing cage polysilsesquioxane photocuring insulating glue, the problem of hole defects caused by bubbles in the coating cannot overflow, and higher insulation reliability, power and high temperature and high humidity resistance are achieved.
Patent Information
- Application Number
- CN202411888993.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-15
AI Technical Summary
The existing photocuring insulating glue cannot overflow the bubbles in the coating after curing, resulting in hole defects and affecting the reliability and power of the components.
Polyurethane acrylate oligomer and fluorine-containing cage-type polysilsesquioxane are used as the main resin to form a dense and stable molecular structure through cross-linking reaction under photocuring conditions, enhancing defoaming and bonding strength.
It effectively avoids the formation of holes in the coating, improves the insulation reliability and power of the components, enhances the high temperature and high humidity resistance, and reduces the curing shrinkage rate.
Smart Images

Figure CN119823700A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cells, and in particular to a light-curing insulating adhesive and a preparation method thereof and application in BC batteries. Background Art
[0002] The new BC (back contact) solar cell, full name is back contact solar cell, has become the mainstream direction of the new generation of solar cell technology due to its higher photoelectric conversion efficiency compared to conventional solar cells. The positive and negative fine grid lines of the BC solar cell are arranged in a forked shape on the back of the cell, the main grid line and the auxiliary fine grid line are printed vertically, the connection between the positive main grid segment and the negative fine grid line is isolated by printing insulating glue, and the connection between the negative main grid segment and the positive fine grid line is isolated by printing insulating glue.
[0003] The insulating glue used on BC batteries usually adopts a thermal curing solution. During the heating and curing process, the viscosity and thixotropy of the coating decrease, and the probability of coating diffusion increases, which will lead to insufficient printing accuracy. At the same time, the thermal curing solution requires a long-term high-temperature channel, and has disadvantages such as complex process and high energy consumption. The insulating glue also adopts a photocuring solution, which has a fast curing speed, no VOC emission problems, and small equipment investment. However, in the screen printing process, due to the high viscosity and thixotropy of the insulating glue, the curing time is short, and the pattern accuracy is improved. At the same time, the bubbles in the coating cannot overflow and will remain in the cured coating, forming hole defects. The holes will increase the risk of component insulation failure. The photocuring insulating glue has higher insulation reliability; in addition, the fast curing characteristics of the photocuring coating make it impossible to release internal stress and cannot better wet the substrate, resulting in poor bonding with the substrate and poor subsequent high temperature and high humidity test performance.
[0004] The patent CN118344767A discloses a photovoltaic insulating adhesive ink composition, which includes an acrylate oligomer, an active monomer and a photopolymerization initiator, wherein the acrylate oligomer includes a first modified acrylate oligomer and a second modified acrylate oligomer, and the mass ratio of the two is 30-50:70-50, the first modified acrylate oligomer includes at least one of an organic silicone acrylate oligomer, a polyether polyurethane acrylate oligomer, and a fluorine-containing acrylate oligomer, and the second modified acrylate oligomer includes at least one of an epoxy acrylate oligomer and a polyester polyurethane acrylate oligomer. Although the patent adopts a first modified acrylate oligomer with low surface tension and a second modified acrylate oligomer with excellent bonding force to cooperate with each other and blend with the active monomer, so that bubbles can be quickly discharged during the curing process to form a coating, thereby avoiding the occurrence of hole defects, the use of multiple acrylate oligomers will increase the cost and complicate the process, and also make the shrinkage of the photocured coating more serious. Summary of the invention
[0005] Based on the technical problems existing in the background technology, the present invention proposes a photocuring insulating adhesive and a preparation method thereof and an application in a BC battery, which solves the defect that bubbles in the coating cannot overflow after the existing photocuring insulating adhesive is cured, resulting in the formation of holes in the coating, thereby improving the reliability and power of the components. The photocuring insulating adhesive not only has better bonding strength with the battery cell, but also can maintain excellent insulation protection effect after high temperature and high humidity testing.
[0006] The light-curing insulating adhesive proposed by the present invention comprises the following raw materials by mass: 40-60 parts of polyurethane acrylate oligomer, 5-15 parts of fluorine-containing cage-type polysilsesquioxane, 20-40 parts of active diluent, 5-25 parts of inorganic nanofiller, and 3-10 parts of photoinitiator;
[0007] The polyurethane acrylate oligomer comprises polyurethane acrylate and organosilicon-modified polyurethane acrylate in a mass ratio of 2-4:1.
[0008] In the present invention, the polyurethane acrylate oligomer includes polyurethane acrylate and silicone-modified polyurethane acrylate. Since the main chain structure of the silicone-modified polyurethane acrylate contains polydimethylsiloxane, it can form good compatibility with the fluorine-containing cage-type polysilsesquioxane with an octahedral cage structure composed of siloxane, thereby ensuring that the two can subsequently undergo a cross-linking reaction under ultraviolet light curing conditions to form a dense and stable molecular structure, thereby obtaining better bonding strength and also being beneficial to enhancing the high temperature and high humidity resistance of the coating.
[0009] Preferably, the polyurethane acrylate is a difunctional polyurethane acrylate.
[0010] Preferably, the organosilicon-modified polyurethane acrylate is obtained by polymerization of terminal hydroxyl polydimethylsiloxane, polyether polyol, polyisocyanate and multifunctional acrylate;
[0011] Preferably, the polyether polyol is at least one of polyethylene glycol, polypropylene glycol or polytetramethylene glycol; the isocyanate is at least one of isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate or 2,4-toluene diisocyanate; and the multifunctional acrylate is at least one of trimethylolpropane triacrylate, pentaerythritol triacrylate or dipentaerythritol pentaacrylate.
[0012] In the present invention, the organosilicon-modified polyurethane acrylate selects terminal hydroxyl polydimethylsiloxane as a monomer to participate in the polymerization, and introduces polydimethylsiloxane into the polyurethane acrylate molecular chain. In addition to being compatible with the fluorine-containing cage-type polysilsesquioxane, it can also increase the flexibility of the chain segment, allowing it to better infiltrate the substrate surface, thereby increasing the adhesion.
[0013] Preferably, the fluorine-containing cage-type polysilsesquioxane is obtained by hydrolyzing and polycondensing a fluorine-containing silane coupling agent and vinyl trichlorosilane;
[0014] Preferably, the fluorine-containing silane coupling agent is at least one of tridecafluorooctyltriethoxysilane, dodecafluoroheptylpropyltrimethoxysilane, trifluoromethyltrimethylsilane or triethyltrifluoromethylsilane;
[0015] Preferably, the weight ratio of the fluorine-containing silane coupling agent to vinyltrichlorosilane is 1-10:1.
[0016] In the present invention, the fluorine-containing cage-type polysilsesquioxane is essentially a cage-like silsesquioxane with alkenyl groups and fluorine-containing carbon chains connected to the periphery. Since it is an octahedral cage structure composed of siloxane, it has a relatively low surface energy. In addition, the fluorine-containing carbon chains connected to the periphery also have hydrophobic and oleophobic properties. Therefore, after the alkenyl groups connected to the periphery and polyurethane acrylate are cross-linked under photocuring conditions, hydrophobic and oleophilic groups can be introduced into the polyurethane acrylate polymer chain, thereby controlling the surface tension of the coating, thereby reducing the generation of bubbles, enhancing the overall defoaming performance of the coating, and avoiding the subsequent formation of holes in the coating.
[0017] Preferably, the reactive diluent is at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, isobornyl acrylate, isobornyl methacrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate or dipentaerythritol pentaacrylate.
[0018] Preferably, the inorganic nanofiller is at least one of silicon dioxide, barium sulfate, bentonite, talc, silica powder or kaolin.
[0019] Preferably, the photoinitiator is at least one of 2-hydroxy-2-methyl-phenylacetone, 1-hydroxy-cyclohexyl benzophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, benzophenone, 2,4,4-trimethylpentylphosphine oxide, diphenylethanedione or 4-phenylbenzophenone.
[0020] Preferably, the raw material further comprises 1-20 parts by mass of pigment and / or additive;
[0021] Preferably, the pigment is at least one of titanium dioxide, phthalocyanine green, cobalt green, yellow iron oxide, cobalt yellow, composite titanium red, cadmium red or iron red, and the auxiliary agent is at least one of a dispersant, a defoamer or a wetting agent.
[0022] The present invention also provides a method for preparing the above-mentioned photocurable insulating adhesive, comprising: stirring and mixing polyurethane acrylate oligomer, fluorine-containing cage polysilsesquioxane, active diluent and inorganic nanofiller at high speed according to mass parts, and then adding photoinitiator and stirring and mixing to obtain the photocurable insulating adhesive.
[0023] The present invention also proposes an application of the above-mentioned light-curing insulating adhesive in BC batteries.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] In the present invention, in the photocurable insulating adhesive, polyurethane acrylate oligomer and fluorine-containing cage-type polysilsesquioxane are used as the main resins. After the cured coating is formed under photocuring conditions, the defoaming property is enhanced due to the introduction of hydrophobic and lipophilic groups, so that bubbles can be quickly discharged during the curing process to form the coating, thereby avoiding the occurrence of hole defects; at the same time, the crosslinking of the polyurethane acrylate oligomer and the fluorine-containing cage-type polysilsesquioxane can further improve the curing degree of the coating to obtain better adhesion and higher operating temperature, and also help to increase the degree of crosslinking and bonding between macromolecular polymer chains, forming a three-dimensional network structure with higher thermal stability, and ultimately solving the problem that bubbles in the coating cannot overflow after the insulating adhesive is photocured, resulting in hole defects in the coating, while also having good insulation performance, reducing the risk of component short circuit, high temperature and high humidity resistance, and can reduce the shrinkage of the insulating adhesive after curing, improve adhesion to the battery cell, and increase the reliability of the component. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram of the structure of the fluorine-containing cage-type polysilsesquioxane described in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0028] Example 1
[0029] A light-curing insulating adhesive, wherein the raw materials include, by mass: 36 parts of difunctional polyurethane acrylate (CN981NS), 15 parts of organosilicon-modified polyurethane acrylate, 10 parts of fluorine-containing cage-type polysilsesquioxane, 15 parts of hydroxyethyl acrylate, 15 parts of trimethylolpropane triacrylate, 15 parts of silicon dioxide, 3 parts of 2-hydroxy-2-methyl-phenylacetone, and 3 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide;
[0030] The organosilicon-modified polyurethane acrylate is prepared according to the following method: 100 parts by mass of polypropylene glycol (PPG-400) is dehydrated at 110° C. and -0.1 MPa vacuum conditions for 1 hour and then cooled to room temperature, 20 parts by mass of double-end alcohol hydroxyl long-chain alkyl silicone oil (IOTA-8865H) is added and stirred and mixed, and then 60 parts by mass of isophorone diisocyanate is added, and the temperature is raised to 80° C. under a nitrogen atmosphere and reacted for 3 hours, and 30 parts by mass of pentaerythritol triacrylate and 0.1 parts by mass of dibutyltin dilaurate are added, and the stirring reaction is continued for 3 hours to obtain the organosilicon-modified polyurethane acrylate;
[0031] The fluorine-containing cage-type polysilsesquioxane is prepared according to the following method: 10 parts by mass of tridecafluorooctyl triethoxysilane is added to 50 parts by mass of tetrahydrofuran and dispersed evenly, 3 parts by mass of deionized water and 2 parts by mass of sodium hydroxide are added, the temperature is raised to 70°C and stirred for reaction for 6 hours, filtered, washed, and dried to obtain fluorine-containing cage-type polysilsesquioxane triol sodium salt; the fluorine-containing cage-type polysilsesquioxane triol sodium salt is added to 100 parts by mass of tetrahydrofuran and dispersed evenly, 1 part by mass of triethylamine and 2 parts by mass of vinyl trichlorosilane are added, the reaction is stirred for 3 hours under an ice-water bath, the temperature is raised to room temperature and the reaction is continued with stirring for 3 hours, the insoluble reactants are removed by suction filtration, rotary evaporation, washing, and drying to obtain the fluorine-containing cage-type polysilsesquioxane. The specific structure is shown in FIG. Figure 1 shown.
[0032] The preparation method of the above-mentioned light-curing insulating adhesive comprises: adding difunctional polyurethane acrylate (CN981NS), silicone-modified polyurethane acrylate, fluorine-containing cage-type polysilsesquioxane, hydroxyethyl acrylate, trimethylolpropane triacrylate and silicon dioxide into a reaction kettle according to mass parts, dispersing them uniformly at a high speed at a rate of 500 r / min, then adding 2-hydroxy-2-methyl-phenylacetone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and dispersing them uniformly at a high speed at a rate of 1000 r / min to obtain the light-curing insulating adhesive.
[0033] Example 2
[0034] A light-curing insulating adhesive, wherein the raw materials include, by mass: 40 parts of difunctional polyurethane acrylate (CN981NS), 20 parts of organosilicon-modified polyurethane acrylate, 15 parts of fluorine-containing cage-type polysilsesquioxane, 10 parts of hydroxyethyl acrylate, 10 parts of trimethylolpropane triacrylate, 25 parts of silicon dioxide, 6 parts of 2-hydroxy-2-methyl-phenylacetone, and 4 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide;
[0035] Wherein, the organosilicon-modified polyurethane acrylate is prepared by referring to the method described in Example 1; and the fluorine-containing cage-type polysilsesquioxane is also prepared by referring to the method described in Example 1.
[0036] The preparation method of the above-mentioned light-curing insulating adhesive comprises: adding difunctional polyurethane acrylate (CN981NS), silicone-modified polyurethane acrylate, fluorine-containing cage-type polysilsesquioxane, hydroxyethyl acrylate, trimethylolpropane triacrylate and silicon dioxide into a reaction kettle according to mass parts, dispersing them uniformly at a high speed at a rate of 500 r / min, then adding 2-hydroxy-2-methyl-phenylacetone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and dispersing them uniformly at a high speed at a rate of 1000 r / min to obtain the light-curing insulating adhesive.
[0037] Example 3
[0038] A light-curing insulating adhesive, wherein the raw materials include, by mass: 32 parts of difunctional polyurethane acrylate (CN981NS), 8 parts of organosilicon-modified polyurethane acrylate, 5 parts of fluorine-containing cage-type polysilsesquioxane, 25 parts of hydroxyethyl acrylate, 15 parts of isobornyl acrylate, 5 parts of silicon dioxide, 2 parts of 2-hydroxy-2-methyl-phenylacetone, and 1 part of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide;
[0039] Wherein, the organosilicon-modified polyurethane acrylate is prepared by referring to the method described in Example 1; and the fluorine-containing cage-type polysilsesquioxane is also prepared by referring to the method described in Example 1.
[0040] The preparation method of the above-mentioned photocurable insulating adhesive comprises: adding difunctional polyurethane acrylate (CN981NS), silicone-modified polyurethane acrylate, fluorine-containing cage-type polysilsesquioxane, hydroxyethyl acrylate, isobornyl acrylate and silicon dioxide into a reaction kettle according to mass parts, dispersing them uniformly at a high speed at a rate of 500 r / min, then adding 2-hydroxy-2-methyl-phenylacetone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and dispersing them uniformly at a high speed at a rate of 1000 r / min to obtain the photocurable insulating adhesive.
[0041] Example 4
[0042] A light-curing insulating adhesive, wherein the raw materials include, by mass: 40 parts of difunctional polyurethane acrylate (CN981NS), 15 parts of organosilicon-modified polyurethane acrylate, 9 parts of fluorine-containing cage-type polysilsesquioxane, 10 parts of hydroxyethyl acrylate, 20 parts of tripropylene glycol diacrylate, 16 parts of talc, 4 parts of 1-hydroxy-cyclohexyl benzophenone, and 2 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide;
[0043] Wherein, the organosilicon-modified polyurethane acrylate is prepared by referring to the method described in Example 1; and the fluorine-containing cage-type polysilsesquioxane is also prepared by referring to the method described in Example 1.
[0044] The preparation method of the above-mentioned light-curing insulating adhesive comprises: adding difunctional polyurethane acrylate (CN981NS), silicone-modified polyurethane acrylate, fluorine-containing cage-type polysilsesquioxane, hydroxyethyl acrylate, tripropylene glycol diacrylate and talcum powder into a reaction kettle according to mass parts, dispersing them uniformly at a high speed at a rate of 500 r / min, then adding 1-hydroxy-cyclohexyl benzophenone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and dispersing them uniformly at a high speed at a rate of 1000 r / min to obtain the light-curing insulating adhesive.
[0045] Comparative Example 1
[0046] A light-curing insulating adhesive, wherein the raw materials include, by mass: 36 parts of difunctional polyurethane acrylate (CN981NS), 15 parts of organosilicon-modified polyurethane acrylate, 15 parts of hydroxyethyl acrylate, 15 parts of trimethylolpropane triacrylate, 15 parts of silicon dioxide, 3 parts of 2-hydroxy-2-methyl-phenylacetone, and 3 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide;
[0047] Wherein, the organosilicon-modified polyurethane acrylate is prepared by referring to the method described in Example 1.
[0048] The preparation method of the above-mentioned light-curing insulating adhesive comprises: adding difunctional polyurethane acrylate (CN981NS), silicone-modified polyurethane acrylate, hydroxyethyl acrylate, trimethylolpropane triacrylate and silicon dioxide into a reaction kettle according to mass parts, dispersing them uniformly at a high speed at a rate of 500 r / min, then adding 2-hydroxy-2-methyl-phenylacetone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and dispersing them uniformly at a high speed at a rate of 1000 r / min to obtain the light-curing insulating adhesive.
[0049] Comparative Example 2
[0050] A light-curing insulating adhesive, the raw materials comprising, by mass: 51 parts of difunctional polyurethane acrylate (CN981NS), 10 parts of fluorine-containing cage-type polysilsesquioxane, 15 parts of hydroxyethyl acrylate, 15 parts of trimethylolpropane triacrylate, 15 parts of silicon dioxide, 3 parts of 2-hydroxy-2-methyl-phenylacetone, and 3 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide;
[0051] Wherein, the fluorine-containing cage-type polysilsesquioxane is prepared by referring to the method described in Example 1.
[0052] The preparation method of the above-mentioned light-curing insulating adhesive comprises: adding difunctional polyurethane acrylate (CN981NS), fluorine-containing cage-type polysilsesquioxane, hydroxyethyl acrylate, trimethylolpropane triacrylate and silicon dioxide into a reaction kettle according to mass parts, dispersing them uniformly at a high speed at a rate of 500r / min, then adding 2-hydroxy-2-methyl-phenylacetone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and dispersing them uniformly at a high speed at a rate of 1000r / min to obtain the light-curing insulating adhesive.
[0053] Comparative Example 3
[0054] A light-curing insulating adhesive, wherein the raw materials include, by mass: 36 parts of difunctional polyurethane acrylate (CN981NS), 15 parts of organosilicon-modified polyurethane acrylate, 10 parts of fluorine-containing cage-type polysilsesquioxane, 15 parts of hydroxyethyl acrylate, 15 parts of trimethylolpropane triacrylate, 15 parts of silicon dioxide, 3 parts of 2-hydroxy-2-methyl-phenylacetone, and 3 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide;
[0055] Wherein, the organosilicon-modified polyurethane acrylate is prepared by referring to the method described in Example 1;
[0056] The fluorine-containing cage-type polysilsesquioxane is prepared according to the following method: 10 parts by mass of tridecafluorooctyltriethoxysilane is added to 50 parts by mass of tetrahydrofuran and dispersed evenly, 3 parts by mass of deionized water and 2 parts by mass of sodium hydroxide are added, the temperature is raised to 70° C. and stirred for reaction for 6 hours, and then an oxalic acid solution (1 mol / L) is added for neutralization, and the insoluble reactants are removed by suction filtration, and the fluorine-containing cage-type polysilsesquioxane is obtained after rotary evaporation, washing, and drying.
[0057] The preparation method of the above-mentioned light-curing insulating adhesive comprises: adding difunctional polyurethane acrylate (CN981NS), silicone-modified polyurethane acrylate, fluorine-containing cage-type polysilsesquioxane, hydroxyethyl acrylate, trimethylolpropane triacrylate and silicon dioxide into a reaction kettle according to mass parts, dispersing them uniformly at a high speed at a rate of 500 r / min, then adding 2-hydroxy-2-methyl-phenylacetone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and dispersing them uniformly at a high speed at a rate of 1000 r / min to obtain the light-curing insulating adhesive.
[0058] Performance Testing:
[0059] The light-curing insulating adhesive obtained in the above examples and comparative examples was coated on the battery cell by screen printing and cured by LED ultraviolet light with a wavelength of 365 nm and a radiation intensity of 4000 mJ / cm 2 , and then conduct various performance tests. The test results are shown in Table 1.
[0060] The pencil hardness refers to the test method of GB / T 6739-2006 "Determination of film hardness of paint and varnish by pencil method"; the module power test refers to the test method of IEC 62446; the volume resistivity refers to the test method of GB / T1410-2006 "Volume resistivity and surface resistivity of solid insulating materials"; the peel strength with EVA refers to the test method of GB / T2790 "Adhesive 180° Peel Strength Test Method Flexible Material to Rigid Material"; the yellowing resistance refers to the test method of GB / T 19394 "Photovoltaic (PV) Module UV Test"; the heat and humidity aging resistance is to put the sample in a high temperature and high humidity oven, and test the peel strength with EVA after placing it at 85℃ and 85% relative humidity for 1000h;
[0061] Table 1 Performance test results of the light-curing insulating adhesives described in the examples and comparative examples
[0062]
[0063] It can be seen from the above table that, compared with the comparative example, the present invention solves the defect that bubbles in the coating cannot overflow after the insulating glue is photocured, resulting in the formation of holes in the coating, while improving the power of the photovoltaic module and reducing the risk of module short circuit. It also has good insulation performance and bonding strength, high temperature and high humidity resistance, and can reduce curing shrinkage.
[0064] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A light-curing insulating adhesive, characterized in that: The raw materials include, by mass: 40-60 parts of polyurethane acrylate oligomer, 5-15 parts of fluorine-containing cage-type polysilsesquioxane, 20-40 parts of active diluent, 5-25 parts of inorganic nanofiller, and 3-10 parts of photoinitiator; The polyurethane acrylate oligomer comprises polyurethane acrylate and organosilicon-modified polyurethane acrylate in a mass ratio of 2-4:
1.
2. The light-curing insulating adhesive according to claim 1, characterized in that: The polyurethane acrylate is a difunctional polyurethane acrylate.
3. The light-curing insulating adhesive according to claim 1 or 2, characterized in that: The organosilicon-modified polyurethane acrylate is obtained by polymerization of terminal hydroxyl polydimethylsiloxane, polyether polyol, polyisocyanate and multifunctional acrylate; Preferably, the polyether polyol is at least one of polyethylene glycol, polypropylene glycol or polytetramethylene glycol; the isocyanate is at least one of isophorone diisocyanate, hexamethylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate or 2,4-toluene diisocyanate; and the multifunctional acrylate is at least one of trimethylolpropane triacrylate, pentaerythritol triacrylate or dipentaerythritol pentaacrylate.
4. The light-curing insulating adhesive according to any one of claims 1 to 3, characterized in that: The fluorine-containing cage-type polysilsesquioxane is obtained by hydrolyzing and polycondensing a fluorine-containing silane coupling agent and vinyl trichlorosilane; Preferably, the fluorine-containing silane coupling agent is at least one of tridecafluorooctyltriethoxysilane, dodecafluoroheptylpropyltrimethoxysilane, trifluoromethyltrimethylsilane or triethyltrifluoromethylsilane; Preferably, the weight ratio of the fluorine-containing silane coupling agent to vinyltrichlorosilane is 1-10:
1.
5. The light-curing insulating adhesive according to any one of claims 1 to 4, characterized in that: The active diluent is at least one of hydroxyethyl acrylate, hydroxyethyl methacrylate, isobornyl acrylate, isobornyl methacrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate or dipentaerythritol pentaacrylate.
6. The light-curing insulating adhesive according to any one of claims 1 to 5, characterized in that: The inorganic nanofiller is at least one of silicon dioxide, barium sulfate, bentonite, talc, silica powder or kaolin.
7. The light-curing insulating adhesive according to any one of claims 1 to 6, characterized in that: The photoinitiator is at least one of 2-hydroxy-2-methyl-phenylacetone, 1-hydroxy-cyclohexyl benzophenone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, benzophenone, 2,4,4-trimethylpentylphosphine oxide, diphenylethylene or 4-phenylbenzophenone.
8. The light-curing insulating adhesive according to any one of claims 1 to 7, characterized in that: The raw materials also include 1-20 parts by mass of pigment and / or additives; Preferably, the pigment is at least one of titanium dioxide, phthalocyanine green, cobalt green, yellow iron oxide, cobalt yellow, composite titanium red, cadmium red or iron red, and the auxiliary agent is at least one of a dispersant, a defoamer or a wetting agent.
9. A method for preparing the light-curing insulating adhesive according to any one of claims 1 to 8, characterized in that: include: The polyurethane acrylate oligomer, fluorine-containing cage-type polysilsesquioxane, active diluent and inorganic nanofiller are stirred and mixed evenly at high speed according to parts by mass, and then a photoinitiator is added and stirred and mixed evenly to obtain the light-curing insulating adhesive.
10. Use of the photocurable insulating adhesive according to any one of claims 1 to 8 in BC batteries.
Citation Information
Patent Citations
Insulating ink for photovoltaic module as well as preparation method and application of insulating ink
CN118344767A